The impact of a telephone hotline on suicide attempts and self-injurious behaviors in patients with borderline personality disorder - Buronfosse, Alice; Robin, Marion; Speranza, Mario; Duriez, Philibert; Silva, Jérôme; Corcos, Maurice; Perdereau, Fabienne; Younes, Nadia; Cailhol, Lionel; Gorwood, Philip; Pham-Scottez, Alexandra (Frontiers in Psychiatry, 2024)
Borderline personality disorder is often associated with self-injurious behaviours that cause personal suffering, family distress, and substantial medical costs. Mental health hotlines exist in many countries and have been shown to be effective in some contexts, but none have been specifically designed for borderline patients. The aim of the present study is to evaluate the impact of a 24/7 hotline dedicated to patients with borderline personality disorder on suicide attempts and self-injurious behaviours.We conducted a single-blind, multicentre (9 French centres) clinical trial with stratified randomisation (by age, sex and centre). Patients (N=315) with a diagnosis of borderline personality disorder (according to the SIDP-IV) were randomised into 2 groups with or without access to the hotline in addition to treatment as usual. The number of suicide attempts and selfinjurious behaviours in each group within twelve month were analysed in the "per protocol" population (Student t-tests, 5% significance threshold), adjusting for possible confounders in a multivariate analysis (using Poisson regression). The percentage of patients with suicide attempts and with self-injurious behaviours (and other percentages) were analysed in the per protocol population (χ2 tests or exact Fischer tests, 5% significance threshold).The mean number of suicide attempts was 3 times lower in the hotline group (0.41 vs 1.18, p=0.005) and the mean number of self-injurious behaviours was 9 times lower (0.90 vs 9.5, p=0.006). Multivariate analysis confirmed the effectiveness of the hotline in reducing suicide attempts and self-harm.This study supports the effectiveness of hotlines in reducing self-aggressive behaviour in patients with borderline personality disorder. Such support is easy to use, cheap and flexible, and therefore easy to implement on a large scale.